Examining factors influencing IT outsourcing success in Malaysian organizations - Hussin, Husnayati; Ismail, Zuraini; Suhaimi, Mohd. Adam; Abdul Karim, Noor Shahriza (2006)
In recent years, information technology (IT) outsourcing continues to receive favourable acceptance to maximize organization’s benefits. There is strong concern on the level of success of IT outsourcing endeavours and past researches indicated inconclusive findings on the influencing factors. This research investigates the relationships between partnership quality, service quality and IT outsourcing arrangements and IT outsourcing success. It was tested using a sample from IT managers in 143 Malaysian organizations. The findings of the survey provide evidence that partnership quality and service quality are important predictors for IT outsourcing success, while IT outsourcing arrangement, particularly the degree of integration and the length of the contract, are found to have insignificant influence on IT outsourcing success.